Unprecedented plastic-made personal protective equipment (PPE) debris in river outlets into Jakarta Bay during COVID-19 pandemic. (April 2021) - Cordova, Muhammad Reza; Nurhati, Intan Suci; Riani, Etty; Nurhasanah; Iswari, Marindah Yulia
Abstract: Increased plastic uses during COVID-19 pandemic challenges efforts to reduce marine plastic debris. Despite recent observations of increased plastic-made personal protection equipment (PPE) waste in coastal areas, comparative data before and during the pandemic lacked. We present in situ monitoring data on riverine debris releases into Jakarta Bay, Indonesia, during COVID-19 pandemic relative to the 2016 baseline data. River debris at two river outlets – the Cilincing and Marunda Rivers, revealed a 5% increase in the abundance of debris and a 23–28% decrease in the weight of debris releases in March–April 2020 compared to March–April 2016, suggesting a compositional shift towards lighter debris. Plastics continued to dominate river debris at 46% (abundance) or 57% (weight). Unique to the pandemic, we observed an unprecedented presence of PPE (medical masks, gloves, hazard suits, face shields, raincoats) that accounted for 15–16% of the collected river debris of 780 ± 138 items (abundance) or 0.13 ± 0.02 tons (weight) daily. The observed increased plastic-made PPE in river outlets urges for improved medical waste management of domestic sources during the prolonged pandemic. Highlights: Riverine debris releases into Jakarta Bay during the COVID-19 pandemic were monitored. Riverine debris increased by abundance while decreased by weight during the pandemic. Plastics dominated riverine debris at 46% by abundance and 57% by weight. The presence of plastic-made personal protection equipment was unprecedented during the pandemic. Plastic-made personal protection equipment accounted for 15–16% of the collected river debris.